A PDTPQx:PC61BM blend with pronounced charge-transfer absorption for organic resonant cavity photodetectors – direct arylation polymerization vs. Stille polycondensation. (April 2022) - Vandermeeren, Tom; Liu, Quan; Gielen, Sam; Theunissen, Dries; Frederix, Siebe; Van Landeghem, Melissa; Liu, Zhen; Van den Brande, Niko; D'Haen, Jan; Vanderspikken, Jochen; Lutsen, Laurence; Vandewal, Koen; et al.
Abstract: Because of their intriguing properties for optoelectronic applications, research on organic semiconducting polymers has steadily progressed over the past decades, yielding increasingly fine-tuned (hetero)aromatic polymer backbones. In this work, the push-pull copolymer PDTPQx is synthesized, both via Stille polycondensation and direct arylation polymerization (DArP), permitting comparison of the two procedures. Near-infrared organic photodetectors (OPDs) are constructed based on these different polymer batches in combination with PC61 BM, and their performance was investigated. From the current-voltage characteristics, it is clear that the DArP polymer-based devices outperform those prepared from the Stille polymers, both in terms of dark current density and external quantum efficiency (EQE), and therefore in terms of specific detectivity as well. The relatively high highest occupied molecular orbital energy level of PDTPQx, in combination with the clear charge-transfer absorption band observed for the DArP-based device, is beneficial for application in organic resonant cavity photodetectors. Such OPDs are prepared for the DArP PDTPQx:PC61 BM (1:4) blends with 180 and 210 nm thick bulk heterojunction active layers. EQEs of 2.5% at 1016 nm and 1% at 1140 nm are achieved, with full-width-at-half-maximum peak responses of 44 and 45 nm, respectively, and detectivities of 2.24 × 10 10 and 1.06 × 10 10 Jones. Graphical abstract: Image 1 Highlights: Synthesis and characterization of a high-HOMO PDTPQx copolymer. Comparison of Stille vs. direct arylation polymerization (DArP). OPD (cavity) device fabrication, optimization and characterization. Lowest dark current and highest detectivity for the DArP polymer. D * values of 2.24 × 10 10 Jones at 1016 nm and 1.06 × 10 10 Jones at 1140 nm (FWHM ∼45 nm).